PERANAN ORANG TUA DALAM MENANAMKAN NILAI RELIGIUSITAS KEPADA ANAK DI TATAARAN DUA KECAMATAN TONDANO SELATAN KABUPATEN MINAHASA SULAWESI UTARA - Widya Sari Karo Karo; V.E.T Salem; A. R. Umaternate (JURNAL PARADIGMA : Journal of Sociology Research and Education, 2022)
The purpose of this study was to determine the role of parents in instilling religious values in children in Tataaran, two southern Tondano sub-districts, Minahasa district, North Sulawesi. The method used in this research is a qualitative research method, which means the process of understanding and obtaining the meaning of individual and group behavior, describing social problems or humanitarian problems. By using data collection techniques are interviews and observations. The informants in this study were parents who had teenage children. From the results of the study it was found that the role of parents in instilling religious values in children had an impact on the behavior and character of children, however, not all values taught were carried out by children. There are several obstacles experienced by parents in instilling religious values in children such as the attitude of children who are indifferent, environmental influences and companions